Education And Training On Baby Massage Stimulation To Improve Personal Social Development Of Babies Aged 0-12 Months - Annisa Hasanah; Feny Tunjungsari; Nadika Zahrany; Nadia Paramita Bhakti Putri; Adisti Amalia Suwarno (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2026)
Background: Baby massage is touching children from the age of 0 months to 12 months. Baby massage provides growth and development stimulation and a relaxing effect on babies with the massage method. This not only optimizes the child's growth, but also provides momentum to channel affection and attention as well as providing a relaxing effect on the baby so that it can improve personal and social development. RSU UMM is one of the hospitals that has a growth and development clinic for monitoring growth and development, especially in babies 0-12 months. Objective: The aim of this service is to increase knowledge and skills about baby massage stimulation for the personal social development of babies 0-12 months at RSU UMM. Method: The method used was to provide education and training to parents of babies aged 0-12 months at RSU UMM, and assess knowledge before and after counseling through questionnaires. Results: Educational Activities and Training on Baby Massage Stimulation to Improve the Personal Social Development of Babies Aged 0-12 Months at RSU UMM, with 5 pairs of parents (10 people) participating. The average value of the initial questionnaire was 49, and the final questionnaire was 72, with a Paired T-test sig.0.041 (<0.05). Conclusion: Education and Training on Baby Massage Stimulation has been implemented to Improve the Personal Social Development of Babies Aged 0-12 Months at RSU UMM with the result of a significant increase in the knowledge of parents of babies aged 0-12 months regarding baby massage stimulation. Key words: education and training, baby massage, personal social development